The Role or Impact of Ahlussunah Wal Jamaah and its Affiliates in Indonesia on Inkarsunnah - Tia Utami; Makmur Hidayat; Dadah Dadah; Muhammad Al Mighwar (al-Afkar, Journal For Islamic Studies, 2026)
The Inkarsunnah movement defined as the rejection of Sunah as a legal source in Islam is a significant deviation from the proper methodology of understanding religion. In Indonesia, this ideology has spread through academic and digital channels, rooted in extreme rationalism and historical criticism of hadith. This study aims to trace the ideological roots of Inkarsunnah and analyze the strategic role of Ahlussunnah wal Jamaah in countering its influence. Using a qualitative-descriptive approach and library research method, the findings show that Ahlussunnah wal Jamaah has responded through educational institutions, scholarly publications, and media-based da’wah. These efforts have significantly contributed to preserving the authority of Sunah and protecting Islamic creed. Rejection of Sunah not only undermines Islamic law but also threatens the foundational structure of Islamic civilization. Therefore, strengthening the salafi methodology in education and da’wah is a strategic necessity.